European multicenter study for the evaluation of a dual-layer flow-diverting stent for treatment of wide-neck intracranial aneurysms: the European flow-redirection intraluminal device study - Killer-Oberpfalzer, Monika; Möhlenbruch, Markus Alfred (American journal of neuroradiology, 2018)
Endoluminal reconstruction with flow-diverting stents represents a widely accepted technique for the treatment of complex intracranial aneurysms. This European registry study analyzed the initial experience of 15 neurovascular centers with the Flow-Redirection Intraluminal Device (FRED) system.
Gesehen am 18.10.2019